KEADAAN SOSIAL EKONOMI RUMAHTANGGA MIGRAN PEREMPUAN DI DESA MISKIN WILAYAH BALI TIMUR - Sri Astiti, Ni Wayan (Jurnal Studi Jender SRIKANDI; Vol. 4, No. 1 Januari 2005, 2012)
Female migrants from the research location ? a poor village in the regency of Karangasem ? do not come from landless households (average hausehold property is 0,75 ha) and their families live in a (semi) permanent house. The main push factor that makes women migrate is the infertility of the dry soil and the lack of job opportunities outside the agricultural sector. The womwn primarily migrate to Gianyar, Denpasar and even as far as Surabaya to increase their income (57,5%) or household welare (25%). Consequently the largest part of household income comes from economic activity outside agriculture (78,9%). The womwn to go the city either because encouraged to do so by relativesm friends, or a broker, and a few go on their own initiative
Keywords: EKONOMI